2013
DOI: 10.1107/s0907444913013802
|View full text |Cite
|
Sign up to set email alerts
|

Putative dioxygen-binding sites and recognition of tigecycline and minocycline in the tetracycline-degrading monooxygenase TetX

Abstract: Expression of the aromatic hydroxylase TetX under aerobic conditions confers bacterial resistance against tetracycline antibiotics. Hydroxylation inactivates and degrades tetracyclines, preventing inhibition of the prokaryotic ribosome. X-ray crystal structure analyses of TetX in complex with the second-generation and third-generation tetracyclines minocycline and tigecycline at 2.18 and 2.30 Å resolution, respectively, explain why both clinically potent antibiotics are suitable substrates. Both tetracyclines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…In a study by Oravcova et al [ 75 ], enterococci harboring the van A gene were frequently identified in TWW, which indicates that these bacteria are not effectively eliminated during wastewater treatment. The high coefficients of correlation between the abundance of genes specific to BFG and genes encoding resistance to tetracyclines, MLS antibiotics, beta-lactams, and the bex A gene confirm previous findings that BFG bacteria are a major reservoir of these ARGs [ 24 , 76 , 77 ]. In the current study, close correlations were found between the prevalence of all analyzed ARGs in environmental samples (r = 0.63–0.98, p < 0.05).…”
Section: Resultssupporting
confidence: 86%
“…In a study by Oravcova et al [ 75 ], enterococci harboring the van A gene were frequently identified in TWW, which indicates that these bacteria are not effectively eliminated during wastewater treatment. The high coefficients of correlation between the abundance of genes specific to BFG and genes encoding resistance to tetracyclines, MLS antibiotics, beta-lactams, and the bex A gene confirm previous findings that BFG bacteria are a major reservoir of these ARGs [ 24 , 76 , 77 ]. In the current study, close correlations were found between the prevalence of all analyzed ARGs in environmental samples (r = 0.63–0.98, p < 0.05).…”
Section: Resultssupporting
confidence: 86%
“…Surprisingly, chlortetracycline binds to Tet(50) in a ∼180° rotated orientation compared to the orientation in which chlortetracycline and other tetracycline substrates ( e.g. iodtetracycline, minocycline, tigecycline) bind Tet(X) 27,38 (Fig. 3a-d and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…TGC (orange) and FAD (gold) are indicated. The crystal structure of Tet(X) (PDB accession number 4A6N ) is based on data from reference 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The other two amino acid residues were closer to the putative O 2 binding pockets. T280A has been previously suggested to interfere with O 2 diffusion ( 41 ). Therefore, other mutations (T281A, V285E, and L287V) from our screen that are located close to those hydrophobic pockets might also affect O 2 transport within the enzyme.…”
Section: Discussionmentioning
confidence: 99%